Obesity associated pro-fibrotic protein augments fibrosis in heart. (25th November 2020) - Tsukano, Y; Shimizu, I; Yoshida, Y; Hsiao, Y; Ikegami, R; Hayashi, Y; Suda, M; Katsuumi, G; Nakao, M; Minamino, T
Abstract: : Chronic sterile inflammation in visceral fat has causal roles for systemic metabolic disorders in obesity. Inflamed visceral adipose tissue secretes pro-inflammatory adipokines, and this contributes to tissue remodeling under a metabolically stressed condition. Various kinds of white adipokines are broadly studied, however, roles of brown adipose tissue (BAT) derived adipokines (BATokine) remain to be explored. In this project, we tried to characterize pathogenic role of BATokine in obesity related fibrotic disorders, especially focusing on heart failure with preserved ejection fraction (HFpEF). For this purpose, we analyzed two sets of DNA microarray data, and identified an obesity associated pro-fibrotic protein (OAFP) as a possible pathogenic BATokine. Our biobank studies showed OAFP increased in patients with diastolic dysfunction, and E/e' analyzed with cardiac echo increased in direct proportion to circulating OAFP level in humans. We generated dietary obese mice model, and found OAFP increased both in BAT and circulation. We generated a murine systemic or BAT specific OAFP knockout (KO) models, and found that obesity-induced diastolic dysfunction ameliorated in these models. Cardiac fibrosis was also suppressed by genetic depletion of OAFP. We found OAFP increased in circulation in aged humans and mice, and studies in chronologically aged mice showed this molecule increased in BAT with aging. Our results indicate that OAFP is secreted predominantly from BAT, and mediates pathogenic roles by augmenting cardiac fibrosis in dietary obesity or aging. Suppression of OAFP may become a therapy for HFpEF. Funding Acknowledgement: Type of funding source: None